The Relationship Between Self-Esteem and Loneliness Among Users of Online Lovers Rental Services on Platform X - Fauziyyah, Amalia Hasna; Andhita Dyorita Khoiryasdien (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
The phenomenon of online lovers rental on platform X reflects a new way of fulfilling social needs in the digital age. This study aims to determine the relationship between self-esteem and loneliness among users of online lovers rental services on platform X. This study uses a correlational quantitative method with accidental sampling technique. There were 100 participants aged 18-40 years who had used online lovers rental services on platform X.  The research instruments used a modified loneliness scale from the UCLA Loneliness Scale Version 3 (29 items, α = 0.947) and a modified self-esteem scale from the Coopersmith scale (32 items, α = 0.916). Data analysis used the Product Moment correlation technique. The results showed a significant positive relationship between self-esteem and loneliness (r = 0.263; p = 0.008), which means that the higher the self-esteem of online lovers rental users, the higher the level of loneliness they felt. This contradicts the common assumption that people who are confident and value themselves are not prone to loneliness. This finding reveals the reality in the digital age that numerous virtual connections, including through online lovers rental services, are unable to significantly reduce a person's feelings of loneliness, which leads readers to analyze how virtual intimacy platforms shape users' emotional experiences in the digital era.